Identification of the risks in CAR T-cell therapy clinical trials in China: a Delphi study. (October 2020) - Wu, Weijia; Huo, Yan; Ding, Xueying; Zhou, Yuhong; Gu, Shengying; Gao, Yuan
Aims: Within the past few years, there has been tremendous growth in clinical trials of chimeric antigen receptor (CAR) T-cell therapies. Unlike those of many small-molecule pharmaceuticals, CAR T-cell therapy clinical trials are fraught with risks due to the use of live cell products. The aim of this study is to reach a consensus with experts on the most relevant set of risks that practically occur in CAR T-cell therapy clinical trials. Methods: A Delphi method of consensus development was used to identify the risks in CAR T-cell therapy clinical trials, comprising three survey rounds. The expert panel consisted of principal investigators, clinical research physicians, members of institutional ethics committees, and Good Clinical Practice managers. Results: Of the 24 experts invited to participate in this Delphi study, 20 participants completed Round 1, Round 2, and Round 3. Finally, consensus (defined as >80% agreement) was achieved for 54 risks relating to CAR T-cell clinical trials. Effective interventions related to these risks are needed to ensure the proper protection of subject health and safety. Conclusion: The Delphi method was successful in gaining a consensus on risks relevant to CAR T-cell clinical trials in a geographically diverse expert association. It is hoped that this work can benefit future risk-based quality management in clinical trials and can potentially promote the better development of CAR T-cell therapy products.